Can Honorific Awards Give Us Clues about the Connection between Socioeconomic Status and Mortality? - Link, Bruce G.; Carpiano, Richard M.; Weden, Margaret M. (American Sociological Review, 2013)
Social epidemiologists Marmot and Wilkinson argue that relative deprivation is the dominant mechanism through which socioeconomic status (SES) affects mortality. If such an argument is valid, we would expect to consistently see the influence of relative deprivation in situations where two or more highly qualified and very similar individuals are nominated in a status competition, but only one receives the status boost conferred by winning. We studied mortality experiences of Emmy Award winners, Baseball Hall of Fame inductees, and presidents and vice presidents—comparing each to nominated losers in the same competition. Our findings and results of similar studies fail to show consistent advantages for winners. The association between winning and longevity is sometimes positive, sometimes negative, and sometimes nonexistent. We conclude that the critical processes determining the strength and direction of any status effect on longevity are changes in life circumstances that result from winning or losing, rather than the processes that inexorably flow from one’s relative position in a status hierarchy.